Synthesis of a novel bioactive glass using the ultrasonic energy assisted hydrothermal method and their biocompatibility evaluation. Issue 16 (28th August 2014) - Sarkar, Swapan Kumar; Sadiasa, Alexander; Lee, Byong Taek
Abstract